Experimental analysis of a thermoactive underground railway station. (March 2022) - Zannin, Jacopo; Ferrari, Alessio; Kazerani, Tohid; Koliji, Azad; Laloui, Lyesse
Abstract: Little is known about the real energy potential of thermoactive underground infrastructures, such as railway stations, that can act as a heating/cooling provider for the built environment. This study presents the results of thermomechanical full-scale in situ testing and numerical analysis of a thermoactive underground train station. The thermal performance and related geostructural impact of a portion of the new underground energy infrastructure (UEI) installed at the Lancy-Bachet train station in Geneva (Switzerland) are analyzed. Heating and cooling tests simulating real operative geothermal conditions are considered. Particular attention is given to ( i ) the monitored wall–tunnel hydrothermal interactions, ( ii ) the thermal response of the UEI to heating/cooling thermal inputs and ( iii ) the thermomechanical behavior of the energy geostructure. Among the main results of this study, it is shown how the hydrothermal tunnel behavior considerably varies on a seasonal basis, while the train circulation completely drives the airflow in the tunnel. The UEI shows a strong heat storage potential due to the main conductive heat transfers between the geostructure and soil, while lower heat fluxes are detected at the wall–tunnel interface. The extraction potential is of lower magnitude with respect to storage because of the limited range of operative fluid temperatures and of the concurrent action of temperature variations at the tunnel boundaries affecting the materials within the UEI. Preliminary guidelines for the thermal response test execution on underground thermoactive infrastructures are also reported. The monitored thermomechanical behavior suggests different wall behaviors in the vertical and longitudinal directions. Low-magnitude strains are recorded, while the mechanical capacity of the existing geostructure can satisfactorily sustain concurrent thermomechanical actions. Highlights: Full-scale in-situ investigations on underground energy infrastructures involves coupled THM aspects. Hydrothermal infrastructure monitoring allows to understand how it affects geothermal operations. Heat storage and extraction potential is affected also by the hydrothermal conditions at air interfaces. Guidelines on thermal response test execution for underground infrastructures are proposed. Thermomechanical behavior of the retaining walls involve thermally-induced axial and flexural actions.